Adherence among Patients with Hypertension at Jayapura, Indonesia - Titan Anissya Indra; A. Rizki Amelia AP; Fairus Prihatin Idris (An Idea Nursing Journal, 2026)
Background: Hypertension is a major non-communicable disease with high morbidity and mortality. Poor adherence to antihypertensive medication remains a challenge and may be associated with educational level, duration of hypertension, knowledge, attitude, and family support. Objective: This study aimed to identify factors associated with medication adherence among patients with hypertension in the Polma Kodam Clinic catchment area, Jayapura City. Methods: A cross-sectional study was conducted among 234 patients selected from a population of 563 patients with hypertension. Data were collected using structured questionnaires and medical records. Chi-square tests and logistic regression were used for data analysis. Result: Educational level, duration of hypertension, knowledge, attitude, and family support were significantly associated with medication adherence. Duration of hypertension was the strongest associated factor (OR = 7.943), indicating that patients with a longer duration of hypertension had approximately 7.9 times higher odds of medication adherence than those with a shorter duration. Conclusion: Medication adherence among patients with hypertension was associated with several sociodemographic and psychosocial factors, with duration of hypertension being the strongest associated factor.